2021
DOI: 10.1007/s12559-021-09931-9
|View full text |Cite
|
Sign up to set email alerts
|

neurolib: A Simulation Framework for Whole-Brain Neural Mass Modeling

Abstract: Abstractneurolib is a computational framework for whole-brain modeling written in Python. It provides a set of neural mass models that represent the average activity of a brain region on a mesoscopic scale. In a whole-brain network model, brain regions are connected with each other based on biologically informed structural connectivity, i.e., the connectome of the brain. neurolib can load structural and functional datasets, set up a whole-brain model, manage its parameters, simulate it, and organize its output… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 81 publications
0
34
0
Order By: Relevance
“…Finally, these offspring are mutated, added to the total population, and the procedure is repeated until a stopping condition is reached, such as reaching a maximum number of generations. The multi-objective optimization is based on non-dominated sorting and several other evolutionary operators as introduced in Deb et al ( 2002 ) which are implemented in our software package neurolib (Cakan et al, 2021 ) using the evolutionary algorithm framework DEAP (Fortin et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, these offspring are mutated, added to the total population, and the procedure is repeated until a stopping condition is reached, such as reaching a maximum number of generations. The multi-objective optimization is based on non-dominated sorting and several other evolutionary operators as introduced in Deb et al ( 2002 ) which are implemented in our software package neurolib (Cakan et al, 2021 ) using the evolutionary algorithm framework DEAP (Fortin et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…All simulations, the parameter explorations, and the optimization framework including the evolutionary algorithm are implemented as a Python package in our whole-brain neural mass modeling framework neurolib (Cakan et al, 2021 ) which can be found at https://github.com/neurolib-dev/neurolib . The forward Euler method was used for the numerical integration with an integration time step of dt = 0.1 ms.…”
Section: Methodsmentioning
confidence: 99%
“…Another emerging simulator at the whole brain scale level is neurolib (Cakan et al, 2021). Similar to TVB, neurolib provides the end user with a variety of neural mass models, the ability to create networks based on empirical connectivity data and generate simulated signals which can be optimized using parameter fitting methods against empirical data.…”
Section: Simulation Enginesmentioning
confidence: 99%
“…If not mentioned otherwise, simulated time was t = 30 seconds with an integration timestep of dt = 0.01 ms. After integration, time series were subsampled at dt samp = 10 ms. The thalamocortical model was simulated using the neurolib library [56]. neurolib is a computational framework for wholebrain modeling written in Python.…”
Section: Numerical Simulationsmentioning
confidence: 99%